Methods for Designing Devices and Systems of Medical Electronics - V. M. Bandaryk; M. I. Vashkevich; M. V. Davydov; N. S. Davydova; O. B. Zelmanski; P. V. Kamlach; M. M. Mezhennaya; A. N. Osipov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
A brief overview of the results of work in the ﬁeld of “Devices, systems and technologies for medical purposes”, obtained with the direct participation of the authors of the article, is given. The results of the development and research in the ﬁeld of modeling the eﬀects of physical factors on the human body and digital processing of biomedical signals are presented. The principal aspects of the original systems of long-term monitoring of the human condition and control of the musculoskeletal system are presented.